Sistem IoT Pengubah Informasi Running Text Berbasis MQTT dan FreeRTOS - Totok Budioko; Berta Bednar (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2025)
One of the media that is often used to provide information is Running Text. Running Texts that are many in number and far away, it will be difficult if you have to change the information that appears because the changes are made with local Wifi, or Bluetooth. The IoT system to change running text information based on MQTT and FreeRTOS consists of running text implemented using ESP32, FC-16 Dot matix LED module type FC-16, MQTT Borker and desktop application to change Running Text information. Changing information can be done for all Running Texts or for each Running Text. Programming on Running Text uses FreeRTOS multitasking base, while the Desktop application uses Pyhton with the TKInter library. The system was successfully designed and implemented with three Running Texts, an 8x32 dot matrix viewer, and successfully changed the information displayed using the desktop application. Based on the test results, the time to send information is not affected by the number of characters. The average sent time is 0.406 s.